Trends and Patterns in the Use of the Contingent Valuation Method for Conservation: A Bibliometric Analysis (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The Contingent Valuation Method (CVM) remains one of the most widely applied stated preference techniques for assessing the economic value of non-market environmental goods and services, particularly in conservation research. However, a systematic understanding of how this field has evolved regarding research productivity, intellectual structure, and thematic direction remains limited. This study conducts a comprehensive bibliometric analysis of CVM-related publications in conservation between 2000 and 2024, using data retrieved from the Scopus database. VOSviewer and Scopus Analyzer were employed to examine leading authors, publication trends, document types, influential journals, keyword co-occurrence, and citation networks by source type. The results reveal a steady increase in publication output, with notable growth after 2016 and a peak in 2020, reflecting CVM's growing methodological maturity and policy relevance. China, the United States, and Malaysia emerged as major contributors, alongside expanding participation from developing regions. Highly cited works by Loomis, Carson, Hanley, and Hanemann continue to shape the theoretical foundation of CVM, whilst emerging themes highlight applications in ecosystem service valuation, climate change, marine conservation, and sustainable tourism. Ecological Economics was identified as the most influential journal, with growing contributions from interdisciplinary outlets such as Sustainability and the Journal of Environmental Management. Despite these advances, Western dominance and limited synthesis studies indicate a need for greater geographic and conceptual inclusivity. Overall, CVM has evolved into an integrative framework linking ecological, social, and economic dimensions of conservation, with future research encouraged to enhance methodological innovation and cross-regional collaboration.
Keywords: Bibliometric analysis; Contingent Valuation Method; Conservation Ecosystem Services; Environmental Valuation; Environmental Policy